Immunity, Sex Hormones, and Environmental Factors as Determinants of COVID-19 Disparity in Women - Rehman, Suriya; Ravinayagam, Vijaya; Nahvi, Insha; Aldossary, Hanan; Al-Shammari, Maha; Amiri, Mai Saad Al; Kishore, Uday; Al-Suhaimi, Ebtesam A. (Frontiers in Immunology, 2021)
The current pandemic of coronavirus disease 2019 (COVID-19), by SARS-CoV-2 (Severe acute respiratory syndrome virus), has resulted in one of the major outbreaks globally witnessed in the past decades. This outbreak is reported in 235 countries and regions, with increasing total of 118,648,417 confirmed cases and 2,632,348 deaths as on 11th March 2021 according to the World Health Organization. The current scenario and preliminary studies suggest a significant impact of gender in morbidity and mortality, where men are reported at greater risk for severity and morbidity. Although the complete dimension of COVID-19 in humans continues to remain unresolved and the contagiousness of SARS-CoVs focuses on the urgency to study various factors, like, immunological, sex, and other differences, to counterpart the research aimed on individual viruses of current importance. The present article aims to discuss the possible factors like estrogen, angiotensin-converting enzyme 2 gene, a stronger innate immunity response in women, the associated microbiota, and the impact of few environmental factors that may explain the gender-based disparity on the mortality and morbidity of COVID-19 in women.